Militerisasi Agrikultur: Keterlibatan Militer Dalam Program Food Estate Indonesia 2020-2024 - Wildan Faisol; Heri Herdiawanto; Ashabriel Nadiva Candialmeera; Nobel Jihadine; Muhamad Arif (Jurnal Keamanan Nasional, 2025)
The COVID-19 pandemic triggered global food security threats, prompting the Indonesian government to launch the Food Estate as a National Strategic Project. A defining feature of this policy is the active involvement of the military, with the Ministry of Defence appointed as the leading sector. This study analyzes the factors and implications of military involvement in food governance (2020–2024) through Donald Travis’s Pragmatic Civil Control theory. Findings indicate that the government utilized the pandemic as a "political opportunity" to prioritize military command efficiency over civilian bureaucratic processes. While this pragmatic approach seeks rapid results, it reflects "food securitization" that bypasses traditional democratic checks. Evidence shows a significant disconnect between these efficiency goals and reality: the marginalization of Dayak indigenous rights in Central Kalimantan, a lack of public participation, and a shift toward centralized, hierarchical governance. Ultimately, the normalization of the military’s role in civilian spheres risks deepening democratic regression. This study concludes that such pragmatism may revive "dual function" (dwifungsi) patterns, threatening civilian supremacy and the sustainability of Indonesia’s post-Reformasi democratic values.